Biomaterial-assisted biotherapy: A brief review of biomaterials used in drug delivery, vaccine development, gene therapy, and stem cell therapy - Xuejiao Han; Aqu Alu; Hongmei Liu; Yi Shi; Xiawei Wei; Lulu Cai; Yuquan Wei (Bioactive Materials, 2022)
Biotherapy has recently become a hotspot research topic with encouraging prospects in various fields due to a wide range of treatments applications, as demonstrated in preclinical and clinical studies. However, the broad applications of biotherapy have been limited by critical challenges, including the lack of safe and efficient delivery systems and serious side effects. Due to the unique potentials of biomaterials, such as good biocompatibility and bioactive properties, biomaterial-assisted biotherapy has been demonstrated to be an attractive strategy. The biomaterial-based delivery systems possess sufficient packaging capacity and versatile functions, enabling a sustained and localized release of drugs at the target sites. Furthermore, the biomaterials can provide a niche with specific extracellular conditions for the proliferation, differentiation, attachment, and migration of stem cells, leading to tissue regeneration. In this review, the state-of-the-art studies on the applications of biomaterials in biotherapy, including drug delivery, vaccine development, gene therapy, and stem cell therapy, have been summarized. The challenges and an outlook of biomaterial-assisted biotherapies have also been discussed.